2020
DOI: 10.1109/access.2020.2976725
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Textual Features-Based Stock Market Prediction

Abstract: Due to its dynamics, non-linearity and complexity nature, stock market is inherently difficult to predict. One of the attractive objectives is to predict stock market movement direction by using public sentiments analysis. However, there is an active debate about the usefulness of this approach and the strength of causality between stock market trends and sentiments. The opinions of researchers range from rejecting the relationship to confirming a clear causality between sentiments and trading in stock markets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The following study used Twitter data to predict six NASDAQ companies' ups and downtrends [38]. First, a methodology was proposed that starts by extracting various text-based resources to enrich the representation of feelings.…”
Section: Discussion Of Workmentioning
confidence: 99%
“…The following study used Twitter data to predict six NASDAQ companies' ups and downtrends [38]. First, a methodology was proposed that starts by extracting various text-based resources to enrich the representation of feelings.…”
Section: Discussion Of Workmentioning
confidence: 99%
“…Moreover, a few studies have used Latent Dirichlet Allocation (LDA) [82][83][84]., where words are viewed as a probabilistic collection of concepts, and the concepts are used as features [82][83][84]. Some works [44,76,79] used the N-grams technique. N-grams is the contagious collection of N words from a given sequence of text.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Ruan et al 36 analysed the sensitivity of hyperparameters in the LSTM method and found that the approach yields an optimal result when the hidden size is set between 250 and 260. Bouktif et al 37 used sentiment‐based stock market prediction utilising the deep learning method. The suggested approach excelled sufficiently and forecasted stock movements with a greater accuracy of 60%.…”
Section: Introductionmentioning
confidence: 99%